Ranciere’s Challenge for the Lithuanian Modern Art Histories: The Possibility of New Sensible Structures - Rybačiauskaitė, Karolina (Problemos, 2020)
By analysing Jacques Rancière’s conception of art regimes and taking the practical example of paintings by Lithuanian artist Vincas Kisarauskas, it is demonstrated that by thinking about the modern art in the 20th century as the intersection of the three art regimes by Rancière, we might escape from the binary oppositions still prevailing in the interpretations of modern art in post-soviet and post-socialist countries, and also escape the current narratives of late and silent modernisms implying the belatedness and disability of modern art created in Soviet Lithuania. By writing histories of modern art with Rancière, it is possible to claim that at least a part of Lithuanian modern art is neither late nor silent. On the contrary, the part operating in the aesthetic regime of art becomes a space of search for the new tropes of expression and of the common sensual fabric of life.